Pengaruh Penggunaan Birth Ball Terhadap Penurunan Nyeri Punggung Bawah Pada Ibu Hamil Trimester III - Risa Safitri (2021)
Back pain is an inconvenience that is often found in pregnant women, especially pregnant women in the third trimester. This study uses the one group pretest-posttest method by giving pretest to respondents before doing birth ball therapy to determine the initial pain degree in respondents and giving posttest after intervention. The purpose of this study was to determine the effect of using a birthball on reducing low back pain in third trimester pregnant women. Data collection was carried out 2 times, namely at the pretest at the first meeting and posttest at the last meeting. The sample of this study was the third trimester pregnant women, totaling 27 pregnant women in Cikembar Village who met the research criteria. Analysis of the data used in this study was univariate analysis conducted to determine the pain scale of pregnant women before and after the intervention, while bivariate analysis was carried out using the Wilcoxon test to determine the effect of using birth balls on pregnant women, with the results showing that the p-value was 0.000.